Equitable Relief Under Civil RICO: Reflection on Religious Technology Center v. Wallersheim: Will Civil RICO Be Effective Only Against White-Collar Crime? - Blakey, G. Robert (1987)
The Court of Appeals for the Ninth Circuit held in Religious Technology Center v. Wollersheim that Congress did not intend to give private civil RICO plaintiffs any right to injunctive relief. This Article argues that the Wollershiem’s reasoning is flawed for being inconsistent with the text, the legislative history, and the purpose of RICO. In addition, it argues that it is inconsistent with statutory interpretation principles advanced by the Supreme Court. In particular, it discusses the case’s facts, provides an overview of civil RICO, examines and critiques Wollersheim’s reasoning, and addresses the adverse policy, economic, and political consequences of Wollersheim, concluding that other courts should not follow Wollersheim